A Case of Anti-NMDA Receptor Encephalitis Treated with ECT. Issue 5 (September 2015) - JONES, KRISTIN C.; SCHWARTZ, ANN C.; HERMIDA, ADRIANA P.; KAHN, DAVID A.
<x xml:space="preserve">Abstract</x> We describe the case of a 17-year-old male who presented with acute onset of seizures and malignant catatonia with psychosis, agitation, and hypermetabolism, who responded to electroconvulsive therapy (ECT). Soon after he began to respond, he was diagnosed with anti-N-methyl-D-aspartate (NMDA) receptor encephalitis and then given immunosuppressive therapy. Anti-NMDA receptor encephalitis is an increasingly recognized autoimmune disorder that often presents with neuropsychiatric symptoms. The mainstays for treatment have been early diagnosis, tumor work-up and removal if found, and initiation of immunosuppressive therapy. Treatment response is often slow and residual symptoms common. In this case, ECT produced clinical stabilization before the underlying diagnosis of anti-NMDA receptor encephalitis was made and standard treatment initiated. We suggest that ECT may be highly beneficial for stabilizing life-threatening neuropsychiatric symptoms in this syndrome and should be considered as a potentially additive treatment to immunotherapy when rapid relief is sought.